PENGARUH TAYANGAN STAND UP COMEDY INDONESIA SEASON 7 DI KOMPAS TV TERHADAP PERSEPSI KOMIKA KOMUNITAS STAND UP INDO PKU - Dani Abdillah; Evawani Elysa Lubis Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Various programs are presented by television stations. They are competing to be able to present interesting and interesting programs for many people. One of is The program of Stand Up Comedy Indonesia Season 7 in Kompas TV tells us that competition comedy is in different style from the others. This comedy program also has the tagline "let 's make club". The theory in this research is Theory of S-R (Stimulus – Response). The purpose of this research is to find out how strong the influence of stand up comedy indonesian season 7 on kompas tv toward the perception of comic stand up indo pku. The method used in this research was quantitative with used sensus sampling technique and total of sample as many as 58 respondents. Technique of data accumulation in this research did by way of spread a questionnaire directly to respondents. To know an influence between X variable and Y variable, researcher used analysis of simple regression linear and to process the data result of questionnaire, researcher used SPSS Program for Windows version 23. Results of this research shows that the influence of stand up comedy indonesian season 7 on kompas tv toward the perception of comic stand up indo pku weak catogory This can be seen from the Model Summary Table which shown determination coefficient (R2) is 0,367 and determination coefficient (Rsquare) is 0,135 as the result from squaring correlation coefficient 0,367 x 0,367. These numbers shows that the influence of stand up comedy indonesian season 7 on kompas tv toward the perception of comic stand up indo pku is 13.5%.Key Words: Stand Up Comedy, Perception, Stand Up INDO PKU